Constructions of binary array set with zero-correlation zone - Ke, Pinhui. (2013)
Based on the perfect binary array and the orthogonal matrix, a new method of constructing zero-correlation zone binary array set is proposed, yielding binary array sets with member sizes almost achieve the theoretical upper bound. A recursive construction of zero-correlation zone binary array set is also proposed and the obtained array sets have even larger sizes as well as additional good correlation properties.